Lower Eyelid Management in Facial Paralysis - Jowett, Nate (Facial Plastic Surgery, 2022)
Correction of lower eyelid retraction is necessary to restore adequate blink in paralytic lagophthalmos. A plethora of static and dynamic surgical techniques have been described for lower eyelid repositioning. This article provides an approach to management of the paralytic lower eyelid, including a summary of existing techniques, case examples, and surgical technique for in-office lower eyelid suspension using a palmaris longus tendon graft.
Keywords: facial paralysis; eyelids; plastic surgery; paralytic lagophthalmos; lower eyelid retraction